6a-2=7

Simple and best practice solution for 6a-2=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6a-2=7 equation:


Simplifying
6a + -2 = 7

Reorder the terms:
-2 + 6a = 7

Solving
-2 + 6a = 7

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 6a = 7 + 2

Combine like terms: -2 + 2 = 0
0 + 6a = 7 + 2
6a = 7 + 2

Combine like terms: 7 + 2 = 9
6a = 9

Divide each side by '6'.
a = 1.5

Simplifying
a = 1.5

See similar equations:

| x-1/3-× | | 0(4/x)(2/3) | | 4(2l+10)=88 | | 100y-y-10=0 | | 3(a-3)=60 | | x^2-21x+17=0 | | 5x+3=13+e | | x-9=79 | | x-19=299 | | 10f+8=33 | | 8s^2-2s-7s=0 | | 27-x=29 | | x-71=100 | | a/2.5=13/10 | | (q-3)*3=24 | | x-8=48 | | x+5=44 | | x-2=40 | | x+4=356 | | X/5=2/5 | | x-32=199 | | W/3=2/5 | | (x/3-2)(3/4x-24)=0 | | 6+7(6g)-5= | | x+24=200 | | x+13=56 | | 60+60*1+1=61 | | (D^4-2D^2+1)y=0 | | 16y-3=10-10y | | 5.4(2x-7)=-18.5 | | -7-2+4q+3q= | | 5e+8=33 |

Equations solver categories